3-Hydrcmy-7,8,9,10-tetrahydro-6H-benzo[c]chromen-6-one and 3-hydroxy-6H-benzo[c] chromen-6-one act as on-off selective fluorescent sensors for Iron (III) under in vitro and ex vivo conditions - Shukur, Karar; Fallah, Amirhossein; Terali, Kerem; Kalkan, Rasime; Gazi, Mustafa; Gulcan, Hayrettin Ozan (Tubitak Scientific & Technological Research Council Turkey, 2021)
Regarding the abundant use of metals for different purposes, it becomes more critical from various scientific and technological perspectives to discover novel agents as selective probes for the detection of specific metals. In our previous studies, we have shown that aqueous solutions of natural urolithins (i.e., hydroxyl-substituted benzolcichromen-6-one derivatives) arc selective Iron (III) sensors in fluorescence assays. In this study, we have extrapolated these findings to another cownarine compound (i.e., 3-Hydroxy-7,8,9,10-tetrahydro-6H-benzo[c]chromen-6-one) and compared the selective metal binding properties with Urolithin B (i.e., 3-Hydroxy-6H-benzo[c]chromen-6-one). Following the synthesis and structure identification studies, the fluoroinetric studies pointed out that the lactam group in the structure still persists to be the important scaffold for maintaining selective on-off sensor capacity that renders the compound a selective Iron (III) binding probe. Moreover, for the first time, fluorescence cellular imaging studies concomitant to cytotoxicity assays with the title compounds were also performed and the results displayed the cell-penetrative, safe, and fluorescent detectable characteristics of the compounds in neuroblastoma and glioblastoma cells through servings as intracellular Iron (III) on-off sensors.
Keywords: Urolithin; fluorescence probe; on-off sensor; Iron (III)